2011
DOI: 10.1007/s10661-011-2012-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the visual quality of green landscaping in rural residential areas: the case of Changzhou, China

Abstract: Changzhou is a typical waterside municipality with approximately 2,500 years of history located south of the Yangtze River. It was an agriculturally oriented region but is becoming an industrialized region. Rural green landscaping in this region possesses characteristics of traditional Chinese gardens. This paper presents a methodology for assessing the visual quality of green landscaping in rural residential areas through public perception-based and expert/design approaches. The former approach enables us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 43 publications
0
50
2
1
Order By: Relevance
“…However, the rating method to real locations is time consuming and expensive, and results are always subjective to different raters (Gupta et al, 2012). In addition, the rating method is also hard to carry out due to the difficulty in recruiting and transporting participants to real locations (Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rating method to real locations is time consuming and expensive, and results are always subjective to different raters (Gupta et al, 2012). In addition, the rating method is also hard to carry out due to the difficulty in recruiting and transporting participants to real locations (Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Using color photographs or slides as surrogates for the natural environment has been chosen as a cost-effective method for evaluating urban greenery (Yao et al, 2012;Meitner, 2004). This method had been validated by various independent studies (Daniel and Boster, 1976;Shuttleworth, 1980;Stamps, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman and Lohr found that all trees with green and red color appearances evoked positive responses [23], but the preference also depends on the environment [29] and other indicators. A landscape rich with colors can give people a better visual experience than a single color [30][31][32]. Seasonal change in color is important [21,32] and the overall landscape color change in spring and summer getting higher scores from evaluators [26].The proportion and distribution of color affects people perceptions and preference for landscapes and people have preferred a natural color pattern [23].…”
mentioning
confidence: 99%
“…Scenes which feature a lack of buildings and technical infrastructure, as well as a lack of fields, would probably be judged as fully harmonious from an aesthetic point of view. They are distinguished by their vividness, high contribution of greenery, and lack of artificial elements recognised as positively correlated to perceived landscape harmony (Arriaza et al, 2004;Clay and Smidt, 2004;Bulut and Yilmaz, 2008;Yao et al, 2014). Their harmony, however, may be diminished by ecological factors such as development in contrast to land relief forms or soil type (Fig.…”
Section: Ildh Versus Other Approaches Of Lh Assessmentmentioning
confidence: 99%